Applying visual analytics to fraud detection using Benford's law. Issue 4 (14th February 2020) - Goh, Clarence
Abstract: Benford's law has been examined as a useful tool for detecting potential accounting fraud. In this article, I provide an introduction to Benford's law and examine how the first digit, second digit, and first‐two digits tests in Benford's law can be employed to detect potential accounting fraud. In addition, I also highlight, through a worked example, how Tableau, a visual analytics tool, can be used to perform Benford's law's first‐digit test to detect potential fraud.